Biofabrication of a novel leukocyte‐fibrin‐platelet membrane as a cells and growth factors delivery platform for tissue engineering applications. (23rd July 2018) - Barbon, Silvia; Stocco, Elena; Grandi, Francesca; Rajendran, Senthilkumar; Borean, Alessio; Pirola, Ivan; Capelli, Stefano; Bagno, Andrea; Tavano, Regina; Contran, Martina; Macchi, Veronica; De Caro, Raffaele; et al.
Abstract: Autologous platelet‐rich hemocomponents have emerged as potential biologic tools for regenerative purpose, but their therapeutic efficacy still remains controversial. This work represents the characterization study of an innovative autologous leukocyte‐fibrin‐platelet membrane (LFPm), which we prepared according to a novel protocol involving multiple cycles of apheresis. The high content in fibrinogen gave to our hemocomponent the appearance of a manipulable and suturable membrane with high elasticity and deformation capacity. Moreover, being highly enriched with platelets, leukocytes, and monocytes/macrophages, the LFPm sustained the local release of bioactive molecules (platelet derived growth factor, vascular endothelial growth factor, interleukin‐10, and tumour necrosis factor alpha). In parallel, the evaluation of stemness potential highlighted also that the LFPm contained cells expressing pluripotency and multipotency markers both at the messenger ribonucleic acid ( NANOG, SOX2, THY1, NT5E, and ENG ) and surface‐protein level (CD44 high /CD73 + /CD34 + /CD117 + /CD31 + ). Finally, biodegradation analysis interestingly showed a good stability of the membrane for at least 3 weeks in vitro and 1 week in vivo. In both cases, biodegradation was associated with progressive exposure of fibrin scaffold, loss/migration of cellular elements, and release of growth factors. Overall, collected evidence could shed some light on the regenerative effect that LFPms may exert after the autologous implant on a defect site.